2020
DOI: 10.1016/j.pmedr.2020.101153
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary, and dietary behaviors associated with indicators of mental health and suicide risk

Abstract: We used data from the 2017 national Youth Risk Behavior Survey to examine associations between physical activity, sedentary, and healthy dietary behaviors and indicators of mental health, suicidal thoughts, and suicidal attempts among a representative sample of US high school students. Sex-stratified logistic regression was used to separately model each mental health-related outcome on the health-related behaviors, while controlling for race/ethnicity, grade, and body weight status. Significant associations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 44 publications
6
34
3
1
Order By: Relevance
“…This shows the potentional importance of promoting school attendance in preventing suicide attempts. Unlike previous research [13,[15][16][17]19,20,[28][29][30], this study did not find that parental and peer support, and physical activity was protective against suicidal behaviour, only high parental support was protective against suicidal ideation in univariate analysis. Despite human resource limitations in providing mental health services in Sierra Leone [11], "mental health services are now freely available in all districts, with mental health nurses stationed in almost all district hospitals providing basic counselling for those with common mental health disorders and where needed, providing referrals for more complex cases.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This shows the potentional importance of promoting school attendance in preventing suicide attempts. Unlike previous research [13,[15][16][17]19,20,[28][29][30], this study did not find that parental and peer support, and physical activity was protective against suicidal behaviour, only high parental support was protective against suicidal ideation in univariate analysis. Despite human resource limitations in providing mental health services in Sierra Leone [11], "mental health services are now freely available in all districts, with mental health nurses stationed in almost all district hospitals providing basic counselling for those with common mental health disorders and where needed, providing referrals for more complex cases.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with previous investigations [12,13,15,16,19,26], this survey found an association between health risk behaviours (trouble from alcohol use, current cannabis use, and/or sedentary behaviour) and suicidal ideation, plans and/or attempts. Some research [14] showed an association between sexual behaviour and suicide attempt, while this study found only in univariate analysis a significant positive association with suicide attempts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, greater financial stress is associated with more undesirable dietary behaviors. Further, poor dietary behaviors lead to undesirable health outcomes such as being overweight or obese [ 16 , 17 ], having a higher risk of suffering from chronic diseases [ 18 , 19 , 20 ], and having a greater likelihood of developing mental health problems [ 21 , 22 ]. In terms of mental health, recent research suggests adults who have been financially disadvantaged by the pandemic are experiencing higher levels of psychological distress than those who have not [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various causes provoked suicide-related behaviors such as poverty, bullying, and weak social relationships, but the suicide rate in South Korea has soared due to the severe stress caused by significant changes in a Western lifestyle based on rapid economic development [ 13 , 22 ]. Numerous risk factors such as old age, low economic status, and self-esteem have been introduced to date, but a lack of studies regarding the role of physical activity in suicidal behaviors may limit confirmation of its effectiveness on suicidal behaviors despite the increases in the importance of PA. Additionally, it is essential to consider that there is a possibility of inaccurate behavioral outcomes based on the types of PA assessment (i.e., questionnaire, accelerometer).…”
Section: Discussionmentioning
confidence: 99%